Transnational cinema in a global north : Nordic cinema in transition - Nestingen, Andrew K.; Elkington, Trevor G. (Trevor Glen); Wright, Rochelle; Schepelern, Peter; Bondebjerg, Ib; Pantti, Mervi; Hjort, Mette; Rugg, Linda Harverty; DuBois, Thomas A.; Iversen, Gunnar; Møller, Birgir Thor; Sørenssen, Bjørn (Detroit : Wayne State University Press, 2005)
"Volume of essays examining the transition from national Nordic cinemas to transnational and global Nordic cinema. Contributors analyze three crucial sites in contemporary Scandinavian cinema: economic change, trends and changes in production cycles, and the most important films of the decade, defined in popular and aesthetic terms"--provided by publisher.
Introduction, Transnational Nordic cinema / Trevor G. Elkington and Andrew Nestingen -- Costumes, adolescence, and dogma : Nordic film and American distribution / Trevor G. Elkington -- "Immigrant film" in Sweden at the millennium / Rochelle Wright -- Film according to dogma : ground rules, obstacles, and liberations / Peter Schepelern -- Danish way : Danish film culture in a European and global perspective / Ib Bondebjerg -- Breaking the borders : Danish coproductions in the 1990s / Pil Gundelach Brandstrup and Eva Novrup Redvall -- Art or industry? : battles over Finnish cinema during the 1990s / Mervi Pantti -- From epiphanic culture to circulation : the dynamics of globalization in Nordic cinema / Mette Hjort -- Globalization and the auteur : Ingmar Bergman projected internationally / Linda Haverty Rugg -- "I'm a lumberjack and I'm okay" : popular films as collective therapy in Markku Pölnen's A Summer by the River / Thomas A. DuBois -- Learning from genre : genre cycles in modern Norwegian cinema / Gunnar Iversen -- Aki Kaurismäki's crossroads : national cinema and the road movie / Andrew Nestingen -- In and out of Reykjavik : framing Iceland in the global daze / Birgir Thor Møller -- Hrafn Gunnlaugsson-- the Viking who came in from the cold? / Bjørn Sørenssen.
Includes bibliographical references and index.
Keywords: Motion pictures -- Scandinavia; film -- Skandinavija; danska kinematografija; švedska kinematografija; norveška kinematografija; finska kinematografija; Bergman, Ingmar; Pölönen, Markku; Kaurismäki, Aki; Gunnlaugsson, Hrafn